Strategy of SME’s development in industry and engineering. - Legeza, Darya; Легеза, Дар’я Георгіївна; Sokil, Yana; Сокіл, Яна Сергіївна; Kulish, Tetyana; Куліш, Тетяна Володимирівна (My University, 2023)
After Ukrainian war it is essential to renovate industry in occupied regions. The purpose of the article is to develop strategy of industry and engineering (the I&E) at the regional level and ground of SMEs’ mission in the industry. Study considers results of interview and focus group. Study of business activity of SMEs and justification of results from the strategy implementation bases on eight elements. Mission, Model, Market, Moment, Men, Machinery, Materials, Money. Mission of SMEs has been changed from planning-oriented to customer-oriented approach during time of Ukrainian independency. Today, numerous entrepreneurs have lost their assets because of occupation. The novelty of the article is revealing the crucial which influence on the eight business elements (8M). Almost all enterprises that produced products have problems entering and maintaining positions in the foreign market, regardless of the strategic vector of foreign economic activity. Recognition of the best companies, international product certification, registration in international professional associations will allow SMEs to improve their position in the foreign market. SMEs use contemporary technologies and equipment of the 70s and 80s of the last century at the same time. The main personnel problems of the region are the outflow of personnel abroad, aging personnel, and intense competition between enterprises in the labor market. The main conditions for opening and activating a business for women are social guarantees from the government, supplementary social working conditions, and security of business activities. Based on the analysis, the strategy of industry of development have four vectors such as Technological progress in value-added chains, Qualified staff and prestigious work, Cooperation of enterprises and stakeholders in value-added chains, Entry and strengthening positions at foreign markets
Keywords: strategy; contemporary technologies; foreign market; Qualified staff; Cooperation of enterprises; Model 8M